1997
DOI: 10.1002/jobm.3620370506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH on the comparative culturability of fungi and bacteria from acidic and less acidic forest soils

Abstract: Under aerobic conditions, the culturable microbial population of acidic forest soils was more tolerant to acidic cultivation conditions than was the culturable microbial population of less acidic soils. The number of culturable bacteria decreased sharply under acidic cultivation conditions, while the number of culturable fungi remained relatively constant over the pH range 2.2-6.5. The ratios of culturable bacteria to culturable fungi were greater than one at pH 6.5; in contrast, the bacteria-to-fungi ratios w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 33 publications
6
23
0
Order By: Relevance
“…The total bacterial and yeast populations were significantly greater pH 6.4 than the two lower pH's, whereas the fungal populations increased when the pH was both reduced to 4.4 or increased to 6.4. This is a logical progression as fungi prefer more acidic and bacteria less acidic conditions and reflects previous results where the number of culturable bacteria decreased sharply under acid cultivation conditions whilst the number of culturable fungi remained relatively constant over a pH range of 2.2-6.5 [17].…”
Section: Microbial Populationssupporting
confidence: 87%
“…The total bacterial and yeast populations were significantly greater pH 6.4 than the two lower pH's, whereas the fungal populations increased when the pH was both reduced to 4.4 or increased to 6.4. This is a logical progression as fungi prefer more acidic and bacteria less acidic conditions and reflects previous results where the number of culturable bacteria decreased sharply under acid cultivation conditions whilst the number of culturable fungi remained relatively constant over a pH range of 2.2-6.5 [17].…”
Section: Microbial Populationssupporting
confidence: 87%
“…Anoxic microsites exist within soils (Smith, 1980 ;Sexstone et al, 1985) and needle litter (van der Lee et al, 1999), and the spontaneous capacity of acidic soils to produce CO # under anoxic conditions is approxi- C. H. Kuhner and others mately one-third of that under oxic conditions (Matthies et al, 1997). A number of anaerobic processes including methanogenesis (Williams & Crawford, 1984 ;Goodwin & Zeikus, 1987 ;Crill et al, 1988), denitrification (Shirey & Sexstone, 1989 ;Blo$ sl & Conrad, 1992 ;Nielsen et al, 1994) and sulfate reduction (Wieder et al, 1990) have been demonstrated to occur in acidic soils.…”
Section: Introductionmentioning
confidence: 99%
“…Given that fungi are more acid tolerant and can metabolize substrates of lower chemical quality (i.e. more recalcitrant to decomposition) than bacteria (Högberg et al 2007;Matthies et al 1997), we should observe bacteriabased food webs under aspen, and fungi-based foodwebs under jack pine. Bacteria generally grow faster and are more nutrient rich than fungi (Wardle 2002), hence we expect higher nutrient and energy cycling rates under aspen.…”
Section: Discussionmentioning
confidence: 98%